Student Character Education Management in Integrated Islamic Elementary Schools - Mira Oktarida; Bukman Lian; Nuril Furkan (Yayasan Sembilan Pemuda Indonesia, 2027)
This study aims to analyze the management of planning, organizing, actuating, and controlling (POAC) character education at SDIT Mush’ab Bin Umair Palembang, including its impacts, obstacles, and solutions in shaping religious values, discipline, and responsibility among students. A qualitative descriptive method was employed, with data collected through observation, in-depth interviews, and documentation. Analysis was conducted systematically to capture managerial processes in character formation during the golden age. Character education management is implemented through the POAC framework as a hidden curriculum. Planning is conducted collaboratively; organizing involves all school members as role models; implementation is based on Islamic habituation; and monitoring is performed authentically. This study offers a comprehensive analysis of elementary school character management facing digital disruption challenges through the synergy of an integrated Islamic curriculum, an underexplored focus in Indonesian educational research. This study provides guidance for educators to manage school ecosystems capable of transforming moral values into students’ intrinsic awareness, addressing parenting inconsistencies between school and home. This research contributes to holistic educational management theory by formulating value integration strategies into modern managerial functions, offering solutions for maintaining student moral integrity amidst rapidly changing social dynamics, and providing actionable insights for school leaders seeking structured, sustainable character education systems.